Design of Multi-Level Inverter Design for Charging Stations of Electric Vehicles - Aung Kyaw Htay; Hla Myo Tun Tun; Devasis Pradhan; Lei Lei Yin Win; Ei Ei Khin; Khaing Thandar Soe (LPPM Universitas Andalas, 2024)
The paper mainly focuses on the Design of Multi-Level Inverter Design for Charging Stations of Electric Vehicles. The research challenges in this study are: the lack of technology for higher level design of multilevel inverter systems for electric vehicles (EVs) is facing to solve the high performance and robustness of the system in reality, the control algorithm for maximum power observing is a crucial challenge in the designing and implementing such kind of multilevel inverter design, the pure sine wave inverter approaches with higher number steps could be a candidate for electric vehicles (EVs) in real world applications. That problems could be solved based on the knowledge and idea of power electronic circuits and systems. The implementation of this study was accomplished based on the specific model especially based on the circuit theory and microelectronic devices. The results confirm that the performance specification of targeted multilevel inverter (MLI) in real world applications.